2019
DOI: 10.1596/1813-9450-8797
|View full text |Cite
|
Sign up to set email alerts
|

Of Governance and Revenue: Participatory Institutions and Tax Compliance in Brazil

Abstract: Traditionally, governments seek to mobilize tax revenues by expanding their enforcement of existing tax regimes and facilitating tax payments. However, enforcement and facilitation can be costly and produce diminishing marginal returns if citizens are unwilling to pay their taxes. This paper addresses gaps in knowledge about tax compliance, by asking a basic question: what explains why citizens and businesses comply with tax rules? To answer this question, the paper shows how the voluntary adoption of two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
4
0
13
Order By: Relevance
“…148 A World Bank study demonstrates that the presence of participatory governance institutions is closely associated with the ability of municipal governments to raise local tax revenue. 149 The research shows that Brazilian municipalities that voluntarily adopt participatory institutions collect significantly higher levels of taxes than other, similar municipalities without these institutions. Similarly, earlier research from Switzerland found that tax compliance is substantially higher in cantons with larger reliance on direct democracy, including fiscal referendums.…”
Section: Accountabilitymentioning
confidence: 89%
“…148 A World Bank study demonstrates that the presence of participatory governance institutions is closely associated with the ability of municipal governments to raise local tax revenue. 149 The research shows that Brazilian municipalities that voluntarily adopt participatory institutions collect significantly higher levels of taxes than other, similar municipalities without these institutions. Similarly, earlier research from Switzerland found that tax compliance is substantially higher in cantons with larger reliance on direct democracy, including fiscal referendums.…”
Section: Accountabilitymentioning
confidence: 89%
“…Таким образом, непосредственное участие граждан в бюджетных решениях стало практическим решением некоторых ключевых проблем, с которыми сталкиваются различные города и территории. По словам авторов, правительства, которые внедряют механизмы гражданского участия, вкладывают средства в демократическую ответственность и легитимность, получают дивиденды в виде налоговых поступлений [8].…”
Section: обзор литературыunclassified
“…En este sentido, especial atención merecen los procesos de presupuestos participativos, donde los individuos deciden el destino de una parte de los recursos municipales, reciben una serie de aprendizajes fruto de su asistencia a las distintas reuniones o asambleas -donde se incluye, entre otros, la estructura del presupuesto municipal y el origen y el destino de los recursos públicos-, y perciben una mayor confianza en el propio ayuntamiento como consecuencia de una mayor transparencia y rendición de cuentas sobre los estados de ejecución de las propuestas referentes a los proyectos votados (Allegretti et al, 2011;Harkins y Escobar, 2015). No obstante, si bien existen diferentes estudios que relacionan la implementación de presupuestos participativos con una mayor recaudación fiscal por parte de las administraciones (Beuermann y Amelina, 2014;Biderman y Silva, 2007;Cabannes, 2004Cabannes, , 2015Mbera y Allegretti, 2014;Schneider y Baquero, 2006;Spada, 2015;Touchton et al, 2019), éstos focalizan la atención en las diferencias en el volumen de ingresos recaudados en regiones con y sin dicho mecanismo, donde la participación de los individuos en sí no es estudiada.…”
Section: Participación Ciudadanaunclassified